Pelatihan Media Non-Digital pada Mata Kuliah Larutan Mahasiswa Semester 3 oleh Praktisi Mengajar - Vindhy Dian Indah Pratika; Faudina Permatasari; Rohmatus Syafiah; Erlia Vrizka (Universitas 45 Surabaya, 2025)
21st century education requires educators to develop innovative and relevant learning media. This service aims to increase science study program students' understanding of the concept of solutions through training and mentoring in the use of non-digital media by independent teaching practitioners. The community service methods used include presentation of material, assistance in creating non-digital learning media, presentations and reviewing media that has been created. This service involves lecturers, teaching practitioners and 3rd semester students who teach solution courses. The results of the service show that the use of non-digital media significantly increases student involvement and understanding of the solution material. Apart from that, this training also improves lecturers' pedagogical skills in integrating non-digital media into learning. This dedication implies the importance of developing creative and interactive learning media to improve the quality of science education in the digital era.